Collagen Remodeling and Fatty Acid Regulation Biomarkers in Understanding the Molecular Pathogenesis of Atrial Fibrillation. (December 2022) - Odeh, Ameer; Dungan, Gabriel D.; Darki, Amir; Hoppensteadt, Debra; Siddiqui, Fakiha; Kantarcioglu, Bulent; Fareed, Jawed; Syed, Mushabbar A.
Introduction: Atrial Fibrillation (AF) is the most common cardiac arrythmia in the world. Structural remodeling and fatty acid metabolism dysregulation are believed to play a role in the development of AF. This study explored different biomarkers in the blood of AF patients and a control population to determine if there was a significant difference between the two groups. Material and Methods: Plasma samples were collected from 73 patients with confirmed diagnosis of AF from Loyola University Clinic. Control group represented commercially available plasma ( n = 50). Sandwich ELISA kits were used to quantify the collagen remodeling proteins and liver type fatty acid binding protein (L-FABP) in the AF population and the control population. Non-esterified fatty acids (NEFAs) were measured using an enzymatic colorimetric kit from Wako Diagnostics. Statistical analyses were performed using GraphPad Prism. Results: All the collagen remodeling biomarkers were significantly higher in AF patients compared to the control group. The fatty acid dysregulation biomarkers were elevated in the AF patients. Spearman correlation analyses yielded significant correlations between L-FABP and TIMP-1 ( r = 0.47, P < 0.001), NEFA and TIMP-2 ( r = 0.41, P = 0.002), NEFA and ICTP ( r = 0.41, P =0 .002), and NEFA and PIIINP ( r = 0.61, P < 0.0001). Summary and Conclusions: The elevation of collagen remodeling biomarkers suggests an upregulation of these biomarkers and their potential role in AF, which may contribute to atrial fibrosis. L-FABP and NEFAs were elevated in AF patients. The correlations between the collagen remodeling and fatty acid dysregulation biomarkers may be due to their involvement in structural remodeling of the atria.